The Relationship Between the Differential Distractors Functioning and the Differential Item Functioning in a Multiple-Choice Mathematics Test - Al Sawalmeh, Yousef; Al Ajlouni, Jehad (Jordan Journal of Educational Sciences, 2019)
This study aimed at examining the relationship between the differential distractors functioning (DDF) and the differential item functioning (DIF) in a multiple-choice mathematics test. The data for the study consisted of the responses of (1540) fifth grade students to (26) multiple choice test items, each with four alternatives measuring basic mathematical skills. Because there was a statistically significant difference in performance on the test due to both, the sex of the student and the location of the school, DDFS software has been used to examine the DDF and DIF in terms of the two variables, through applying the Mantel- Hanzel odds ratio MH-LOR method. The results of the differential item and distractor functioning analysis showed that there are (8) DIF items and (15) DDF distractors in the test in terms of gender or location. With regard to the relationship between DIF and DDF, the results showed a positive relationship between them. It is expected that the item will more likely have DIF with increased probability of containing DDF distractors